Diversidad taxonómica de aves en función de diferentes tipos de vegetación en la Faja Volcánica Transmexicana Occidental - Leal-Aguayo, Hector (2025)
The Trans-Mexican Volcanic Belt (TMVB) in its western section possesses a high biodiversity, resulting from its environmental heterogeneity. However, this biological richness is threatened by diverse anthropogenic pressures, such as deforestation and land use change. With the objective of evaluating the taxonomic diversity of birds in the western TMVB, this study was carried out in two localities of Jalisco: Sierra de Quila Flora and Fauna Protection Area and a sustainable avocado production zone in Zapotlán el Grande. Sampling was carried out in different vegetation types during the years 2021 to 2024, using mist nets and point counts. To evaluate taxonomic diversity, the analysis of taxonomic distinctness was employed. A total of 202 bird species were recorded, where it was observed that the most important taxonomic unit was the order level, with Passeriformes being the most diverse order. Among the different vegetation types, the tropical deciduous forest presented the greatest species richness. Although migration increased bird richness in general, taxonomic diversity decreased. The results also showed that secondary vegetation and agricultural zones have a high taxonomic diversity, which is consistent with the intermediate disturbance hypothesis, which suggests that a moderate disturbance can increase habitat heterogeneity and promote the coexistence of multiple species.